2013
DOI: 10.1590/s0103-65132013005000073
|View full text |Cite
|
Sign up to set email alerts
|

Uma análise exploratória do financiamento público à interação universidade-empresa no Brasil

Abstract: ResumoO artigo explora o tema do financiamento do esforço de inovação das empresas por meio de parcerias com institutos de ciência e tecnologia, os quais, juntos, formam um importante indutor de políticas de fomento à inovação. No caso brasileiro, a combinação dos recursos de fomento federais e estaduais e a infraestrutura montada nas ICTs nas últimas décadas participam na consolidação desse esforço. O artigo traz reflexões sobre a interação universidade-empresa para a inovação a partir de uma survey realizada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Finally, in this area of collaboration university -company, Petrobras stands out as the company which leads university-company research (Alves & Pimenta-Bueno, 2014;Gielfi et al, 2017;Matei et al, 2015). In addition to its importance to Brazil, as reported by Gielfi et al (2017), this emphasis occurs mainly because Petrobras has an extensive network of scientific collaborations dispersed throughout the country.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, in this area of collaboration university -company, Petrobras stands out as the company which leads university-company research (Alves & Pimenta-Bueno, 2014;Gielfi et al, 2017;Matei et al, 2015). In addition to its importance to Brazil, as reported by Gielfi et al (2017), this emphasis occurs mainly because Petrobras has an extensive network of scientific collaborations dispersed throughout the country.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
“…The next paragraphs address the findings of each of these areas. The collaboration between universities and companies as a means to boost OI is the object of research of most of the studies identified (Alves & Pimenta-Bueno, 2014;Castro et al, 2014;Carrijo & Botelho, 2013;Closs & Ferreira, 2012;Fernandes et al, 2016;Gielfi et al, 2017;Matei et al, 2015;Oliveira & Balestrin, 2015;Schaeffer et al, 2015;Silva et al, 2013b;Stal & Fujino, 2016). Closs & Ferreira (2012) point out that university-company collaboration tends to be positive for companies because, in addition to reducing innovation costs, it also allows greater access to qualified people and university structures, especially laboratories.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations